A Switchable Open/closed Polyaromatic Macrocycle that Shows Reversible Binding of Long Hydrophilic Molecules. Issue 38 (9th August 2017) - Kurihara, Kohei; Yazaki, Kohei; Akita, Munetaka; Yoshizawa, Michito
Abstract: In spite of wide‐ranging previous studies on synthetic macrocycles, the installation of open–close functions into the frameworks remains a challenge. We present a new polyaromatic macrocycle capable of switching between open and closed forms in response to external stimuli, namely, base and acid. The macrocycle, which is prepared in three steps, has a well‐defined hydrophobic cavity with a length of around 1 nm, surrounded by four pH‐responsive acridinium panels. The open and closed structures were confirmed by single‐crystal X‐ray analysis. The cylindrical cavity can bind long hydrophilic molecules up to 2.7 nm in length in neutral water and then release the bound guests through a reversible open‐to‐closed structural change upon simple addition of base. Abstract : A dynamic short tube : A polyaromatic macrocycle capable of switching between open and closed forms in response to external stimuli is presented. The macrocycle has a well‐defined hydrophobic cavity around 1 nm in length, surrounded by four pH‐responsive acridinium panels. The cylindrical cavity can bind long hydrophilic molecules in neutral water and then release them through an open‐to‐closed structural change upon addition of base.